Description of Nurses' Perceptions about EWS (Early Warning System) and Its Use in The Inpatient Unit of Pekajangan Islamic Hospital Pekalongan - Toto Eko Santosa; Neti Mustikawati (Prosiding University Research Colloquium, 2022)
Controlling the mortality rate is very important to determine the level of quality standards of hospital services. The Early Warning System (EWS) helps nurses detect deteriorating conditions and identify patient needs so as to reduce mortality. This study aims to describe the perception of nurses about the use of EWS in the inpatient unit of RSI Pekajangan. Quantitative descriptive research design. The sampling technique in this study was total sampling with a total of 53 respondents. The data collection tool uses a questionnaire. The results showed the average age of the respondents was 33.38 years, most of the respondents were female as many as 38 respondents (71.7%), some respondents had Diploma 3 education as many as 48 respondents (90.6%) and the average tenure respondents were 9.75 years old, most respondents had a perception of the EWS in the good category, namely 44 respondents (83.3%) and most respondents had a perception about the use of EWS in the sufficient category, namely 37 respondents (69.8%). The results of this study recommend that nurses are expected to improve their ability in implementing the early warning system (EWS) so that the incidence of cardiac arrest, respiratory arrest and mortality in hospitals can decrease.